THE ROLE OF MINDFULNESS IN SUBJECTIVE WELL-BEING FOR INTERNSHIP DOCTORS - Arum, Kamila Sekar; Purnamaningsih, Esti Hayu (International Journal of Psychosocial Rehabilitation, 2020)
Internship doctors face many stressors such as role conflict within and adjustment to their new working environments. These stressors decrease the doctors’ subjective well-being and can further affect the quality of the health services they provide. One of the factors that influence doctors’ subjective well-being is mindfulness. This research investigated the role of mindfulness for subjective well-being in internship doctors (N = 121). This study used the Positive and Negative Affect Schedule and Satisfaction with Life Scale to measure subjective well-being and a Mindful Attention Awareness Scale scale to measure mindfulness. The results of the study were analyzed using a simple regression analysis technique and the results were R2 = 0.204 and F= 30.519 with p < 0.05. These results indicate that mindfulness has an effective contribution to the subjective variable of welfare by 20.4%. Furthermore, one-way ANOVA suggests internship duration affects doctors’ subjective well-being as well. Doctors who spent 4–6 months as an intern had higher levels of subjective well-being compared to doctors who spent more than ten months in an internship.